Extended spectrum beta-lactamase (ESBL) genotypes in Escherichia coli from patients at the Landspítali University Hospital in Iceland from 2006-2012 - Hildur Byström Guðjónsdóttir 1983- (2014)
Introduction. The prevalence of antibiotic resistance is a growing problem and is a major threat to public health. The first ‘class A’ extended-spectrum β-lactamases (ESBLA), that confer resistance to third-generation cephalosporins, were found in the 1980s as point mutations in the parent enzyme. CTX-M is the newest plasmid-mediated ESBLA, first recognized in 1989 and mostly found in Escherichia coli (E. coli) and Salmonella enterica. The most common ESBL in the world is the CTX-M-15 enzyme, which was first described in 2001 and most commonly found in E. coli. The prevalence of resistance to third-generation cephalosporins is increasing all over the world; the Nordic countries have the lowest reported prevalence. The detection of ESBLs is very important for the diagnosis and treatment of patients. Methods. The objective for this study was to determine the ESBLA genotypes in E. coli bacteria from patients in Landspítali’s inpatient wards, emergency rooms and outpatient clinics. ESBLA-producing E. coli, isolated from all patients during the years 2006-2012, were included in the study sample. All E. coli isolates that have shown ESBLA production have been preserved and stored for future analyses. All isolates selected for this study went through DNA extraction, then PCR with primers for the ESBL genes blaCTX-M, blaSHV and blaTEM, followed by an electrophoresis. Thereafter all PCR positive isolates were sent for sequencing for subgenotyping. Results. A total of 164 isolates, from 120 patients were chosen for this study. There were 150 isolates positive with the CTX-M primer, 13 positive with the SHV primer and 88 positive with the TEM primer. Four isolates were negative with all primers. Genotyping for subtypes was unsuccessful for 23 CTX-M and 3 SHV genes. The results showed 92% of all isolates had the CTX-M enzyme, and thereof 66.7% had CTX-M-15. The high number of ungenotyped CTX-M genes gives reason for further studying the isolates with other primers. Conclusion. This was the first Icelandic study on ESBL ...